If it's not what You are looking for type in the equation solver your own equation and let us solve it.
1.23=z-2
We move all terms to the left:
1.23-(z-2)=0
We get rid of parentheses
-z+2+1.23=0
We add all the numbers together, and all the variables
-1z+3.23=0
We move all terms containing z to the left, all other terms to the right
-z=-3.23
z=-3.23/-1
z=3+0.23/1
| 0=20-2t | | x^2-19=17 | | w/2=2.64 | | 45-180=25y+20 | | 2x+7+x=x+2+x | | 45+2=25y-180 | | 11c+3c+-11c=-9 | | 8−2y=4 | | 2/3(8x+12)=11 | | -3x-6(x-3)=18+2x | | 18w-9w+-7w+-11w+16w=-14 | | v-4.32=8.7 | | |4x+1|-1=20 | | 5=-8w+3(3w+5) | | 2y−3=3y2−10y+12 | | 13.86+0.08h=14.61-0.14h | | 3x=115=3(x+5) | | v+2.41=7.86 | | Y=0.08x2 | | y-5.11=9.2 | | 3x-4=32-x | | r-3+ 3=7 | | y-1.1=7.9 | | b−b+2b+4b−5b=18 | | 6(3x-12)=72 | | 12=x/2-11 | | 10x+4=2x+18 | | 11-x/2=12 | | r/4+-8=-11 | | 15y=11 | | 8+2x=x+0.2x^2/2 | | x/3+11=32 |